Karakteristik Agronomis Tiga Varietas Padi (Oryza sativa L.) pada Dua Sistem Tanam Benih di Lahan Pasang Surut - Kriswantoro, Haris; Safriyani, Etty; ,, Purwaningsih; Herlinda, dan Siti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
The efforts to develop and increase rice production in tidal land need appropriate technologies including adaptable superior varieties and efficient seed planting system. This study was aimed to measure the agronomic characteristic of the three rice varieties on the systems of in-row direct seeding and broadcast in tidal land. The experiment was carried out at type B of tidal land in Sidoharjo Village, Air Saleh Subdistrict, Banyuasin District, from January to April 2016. The experiment was conducted using split plot design with four replications. The main plot was seed planting system, consisted of in-row direct seeding system and broadcast system; whereas subplot was three rice varieties, consisted of  Inpari 22,  Inpara 4, and Ciherang.  Result of LSD test on interaction showed that though the best growth was obtained from the combination of Inpari 22 and in-row direct seeding and  very significant  with the others, but its yield was not significant with the combination of Inpara 4 and in-row direct seeding. It was concluded that Inpari 22 and Inpara 4 with in-row direct seeding system showed better growth and higher yield than Inpari 22, Inpara 4 and Ciherang with broadcast system in tidal lands. Ciherang was not suitable in tidal land, while Inpari 22 was suitable.